Public-Private Dialogue for City Competitiveness : Competitive Cities for Jobs and Growth, Companion Paper 7 - Sivaev, Dmitry; Herzberg, Benjamin; Manchanda, Sumit (World Bank, Washington, DC, 2016)
The objective of this paper is to review and analyze existing literature on Public Private Dialogue (PPD) and the way it can be applied to address the issues of competitiveness at the city level. The paper aims to explain how traditional PPD approaches and techniques should be adjusted for application at the city level.